OPTIMALISASI MEDIA SOSIAL GERAKAN PEMUDA (GP) ANSOR SEBAGAI STRATEGI DAKWAH PIMPINAN CABANG KOTA KEDIRI - Firdaus, Muhammad Mirza; Kolil, Mochamad Taufiq (Universitas Hasyim Asy'ari, 2023)
This study aims to reveal an overview of the proselytizing strategy carried out by the Ansor Kediri Kota youth organization in delivering proselytizing, especially in proselytizing media that transforms by sosial media. One of the implementations of the use of sosial media is as a proselytizing media through digitization impressions, both in the form of photos, videos and entertaining content as well as having the content of proselytizing messages. The research method used is qualitative research with a phenomenological approach. The results of this study show that the optimization of proselytizing through sosial media using the Instagram and Youtube platforms can be well received by young people, especially millennial people. The supporting faktors in the Ansor Youth organization in carrying out this program are the administrators who have indeed as a speech by the depth of basic religious knowledge of islamic boarding schools, the high number of followers owned by some administrators and the determination of contemporary themes. The field challenges currently faced are related to decrease time management or schedules and limited facilities owned. Keywords: Sosial Media, Da'wah Strategy, GP Ansor